The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1016/s0022-5223(97)70184-3
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome after the Fontan operation: Factors influencing late morbidity

Abstract: A poor functional outcome is uncommon after the Fontan operation but becomes more frequent with increasing duration of follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
133
3
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 199 publications
(145 citation statements)
references
References 18 publications
5
133
3
4
Order By: Relevance
“…Although the immediate mortality in this series was higher than that reported in the literature 1,[10][11][12][13]16,17 , the late mortality in our group of patients was similar to that found by other authors 15,19 underwent the right atrium-pulmonary artery or Björk techniques, and found a survival rate of 15 years in about 70%, for both techniques. In our group of patients, a high mortality occurred in the immediate postoperative period.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Although the immediate mortality in this series was higher than that reported in the literature 1,[10][11][12][13]16,17 , the late mortality in our group of patients was similar to that found by other authors 15,19 underwent the right atrium-pulmonary artery or Björk techniques, and found a survival rate of 15 years in about 70%, for both techniques. In our group of patients, a high mortality occurred in the immediate postoperative period.…”
Section: Discussionsupporting
confidence: 88%
“…Our patients were operated on, on the average, at about 5 years of age, as with other groups 16,19,20 ; they had a tendency toward being younger during the last decade of our experience, like in the Toronto 15 and Boston 17 groups. Older age at surgery is a risk factor of late mortality after the Fontan operation, because the prolonged volume overload in the working ventricle and persistent cyanosis contribute to the progressive deterioration of the cardiac muscle 1,19 , although Yeh et al 15 were unable to prove a significant increase in survival by anticipating the moment of surgery.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations